2019
DOI: 10.1002/anie.201813143
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung Reactivity of Ynamides: An Unconventional [1,3]‐Sulfonyl and [1,5]‐Sulfinyl Migration Cascade

Abstract: A regioselective sulfonyl/sulfinyl migration cycloisomerization cascade of alkyne‐tethered ynamides is developed in the presence of XPhosgold catalyst. This reaction is the first example of a general [1,3]‐sulfonyl migration from the nitrogen center to the β‐carbon atom of ynamides, followed by umpolung 5‐endo‐dig cyclization of the ynamide α‐carbon atom to the gold‐activated alkyne, and final deaurative [1,5]‐sulfinylation. This process allows the synthesis of peripherally decorated unconventional 4‐sulfinyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 69 publications
(8 reference statements)
2
30
0
Order By: Relevance
“…However,t oour surprise,t he 2,3-dihydrobenzo[f]indole derivative 10 a (58 %) was obtained from 8awhen subjected to XphosAuNTf 2 in acetone at room temperature.T his path is possible through formal intramolecular tetradehydro-Diels-Alder (TDDA) reaction. [17,20] Notably, 10 a (94 %) was obtained from 8a by treatment with JohnPhosAu(MeCN)SbF 6 (2.0 mol %) in dichloromethane at room temperature for 15 minutes. [15] We believe that the homopropargyl motif is more flexible and does not adopt the geometry necessary for the title reaction to take place,which thus leads to aformal [4+ +2]-TDDAreaction (see the Supporting Infomration for computations).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations
“…However,t oour surprise,t he 2,3-dihydrobenzo[f]indole derivative 10 a (58 %) was obtained from 8awhen subjected to XphosAuNTf 2 in acetone at room temperature.T his path is possible through formal intramolecular tetradehydro-Diels-Alder (TDDA) reaction. [17,20] Notably, 10 a (94 %) was obtained from 8a by treatment with JohnPhosAu(MeCN)SbF 6 (2.0 mol %) in dichloromethane at room temperature for 15 minutes. [15] We believe that the homopropargyl motif is more flexible and does not adopt the geometry necessary for the title reaction to take place,which thus leads to aformal [4+ +2]-TDDAreaction (see the Supporting Infomration for computations).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[15] Detailed survey of Au catalysts, solvents,a dditives,a nd other reaction parameters revealed that the conversion of 1a/1e into 2a (54 %)/2e (82 %), respectively,o ccurred using XPhosAuNTf 2 (5.0 mol %) in acetone at 80 8 8Cf or 8hours [Eq. [17] Thes ubstrate 1f (o-Me) provided a1:1 mixture of atropisomers of 2f.The desired products 2gk were obtained from 1g-k having ab iphenyl and (hetero) aryl/alkyl substituents at the ynamide and propargyl termini, respectively. Thec ompound 1d with alkyl substitution at the propargyl terminus also participated to the cycloisomerization to yield 2d (65 %).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the intramolecular cyclizations of ynamides including transition-metal-catalyzed and Brønsted acid-catalyzed nucleophilic cyclizations, anionic cyclizations and radical cyclizations, have been extensively investigated for synthesis of N-heterocycles (Fig. 3a) [58][59][60][61] . However, the skeletal reorganization of ynamides is rarely reported.…”
mentioning
confidence: 99%